2005
DOI: 10.1248/jhs.51.418
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Magnesium Deficiency on Blood Pressure in Normal Rats Fed Cadmium

Abstract: We attempted to further define the effects of an Mg-deficient diet on blood pressure in rats fed Cd for long periods. Twenty male Wistar rats were grouped according to four different diets: normal diet (N rats); normal diet supplemented with Cd at a dose of 50 µg/g of diet (N rats fed Cd); Mg-deficient diet (D rats); and Mg-deficient diet supplemented with Cd at a dose of 50 µg/g of diet (D rats fed Cd). Each diet was given for 60 days. N rats fed Cd developed a duration-limited increase in blood pressure: by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…9) We have also reported that the route of administration and body burden of Cd used in present study produced increase in blood pressure and plasma aldosterone level. 11,14) Present study by using the moderately Mg-deficient diet demonstrated significant interaction between Mg deficiency and Cd treatment on Cd concentrations in the heart and aorta (Fig.…”
Section: Fig 2 Blood Pressure and Heart Rate In Mg-deficient Rats Tsupporting
confidence: 65%
See 1 more Smart Citation
“…9) We have also reported that the route of administration and body burden of Cd used in present study produced increase in blood pressure and plasma aldosterone level. 11,14) Present study by using the moderately Mg-deficient diet demonstrated significant interaction between Mg deficiency and Cd treatment on Cd concentrations in the heart and aorta (Fig.…”
Section: Fig 2 Blood Pressure and Heart Rate In Mg-deficient Rats Tsupporting
confidence: 65%
“…8) We have recently reported that decreased blood pressure was observed in severe Mg-deficient rats fed Cd. 9) In light of these reports, we speculated that the effects of moderate Mg-deficiency and Cd treatment might interact to affect circulation parameters in rats, which results in increased blood pressure.…”
Section: Introductionmentioning
confidence: 97%